Analisis Pembentukan Kata dan Makna Leksikal Penaman Umbul Di Kabupaten Klaten Serta Relevansinya Sebagai Materi Ajar Teks Deskriptif Peristiwa Budaya di Sekolah Menengah Pertama - Rahmmawati, Rofika Ayu; Suryanto, Edy; Rahadini, Astiana Ajeng (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2023)
This research is based on language learning in understanding a discourse. Morphological analysis and lexical meaning can help students and educators more easily understand discourse, especially descriptive texts of cultural events. Learning descriptive text of cultural events is contained in Basic Competencies, in Grade VII, Junior High School in 2013 curriculum, Central Java Province. In addition, it can enrich new vocabulary, especially in Javanese. Researchers have brought up the naming of umbul  in Klaten Regency with the aim of introducing potential to the younger generation by learning the Javanese language in particular. The name of the umbul  or feather is also suitable as a research object with a study of morphology and lexical meaning. The morphological processes found include: zero derivation, application, abbreviation, composition. The lexical meanings found are described according to the origin of the name umbul  or feathers, which are divided into the following categories: tree names, animal names, leaf names, figures/figures, object names, genus, hamlet name, village name, building, geographical situation, character based on of location near another building, verb, form. The object retrieval technique is targeted sampling and snowball sampling. Data collection techniques using face-to-face or fishing techniques, recording techniques, note-taking techniques. The validity test used theoretical triangulation and data source triangulation from both informants and external supporting data. Data analysis procedures using fixed methods of comparison include: data reduction. Categorization, synthesis, formulation of working hypotheses. The results of the study are relevant for learning descriptive texts of cultural events KD 3.1 understands the content of descriptive texts about cultural events and KD 4.1 Responds to the content of descriptive texts about cultural events, in addition, it can promote the character of students responsible for the environment.